Teatro Praga’s Omission of Shakespeare – An Intercultural Space - Sequeira Mendes, Maria (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
Teatro Praga’s (a Portuguese theatre company) adaptations of A Midsummer Night’s Dream and The Tempest omit what is usually considered crucial to a Shakespearean adaptation by giving primacy to neither text nor plot, nor to a stage design that might highlight the skill and presence of the actors, a decision arguably related to what the company perceives as a type of imprisonment, that of the lines themselves and of the tradition in which these canonical plays have been staged. Such fatigue with a certain way of dealing with Shakespeare is deliberately portrayed and places each production in a space in-between, as it were, which might be described as intercultural. “Inter,” as the OED clarifies, means something “among, amid, in between, in the midst.” Each of Teatro Praga’s Shakespearean adaptations, seems to exist in this “in-between” space, in the sense that they are named after Shakespeare, but are mediated by a combination of subsequent innovations. Shakespeare then emerges, or exists, in the interval between his own plays and the way they have been discussed, quoted, and misquoted across time, shaping the identities of those trying to perform his works and those observing its re-enactments on stage while being shaped himself. The fact that these adaptations only use Shakespeare’s words from time to time leads critics to consider that Teatro Praga is working against Shakespeare (or, to admirers of Henry Purcell, against his compositions). This process, however, reframes Shakespeare’s intercultural legacy and, thus, reinforces its appeal.